Low Body Weight Predicted Bradycardia and Desaturation in Retinopathy of Prematurity Surgeries: A Retrospective Cohort Study - Jiang, Bailin; Yao, Lan; Zhao, Hong; Liang, Jianhong; Feng, Yi (Frontiers in Pediatrics, 2020)
Background: As a leading cause of childhood blindness, the epidemic of retinopathy of prematurity (ROP) in China is characterized by advanced stage of ROP in more mature infants than those in the West. More advanced stage of disease necessitates more complicated surgical procedures and consequently exposure to general anesthesia. These ex-prematurely born infants are at risk of developing desaturation especially after surgery under general anesthesia. Physical status, anesthetic management and surgical profile are three main facets of perioperative setting and need to be investigated to identify useful predictors for perioperative adverse events in this population of fragile infants. Methods: In this retrospective cohort study, we enrolled all infants undergoing ROP surgeries at Peking University People’s Hospital, Beijing, China from November 1, 2016 to October 31, 2017. Physical status, anesthesia and surgical management were analyzed by exploratory factor analysis and component matrix to explore risk factors for adverse events. Results: During the 12 months, 267 cases were included, among whom 61 infants underwent two surgeries required by their ophthalmological conditions. The median postconceptual age at the time of surgery was 46 (40, 53) weeks, and median body weight was 4.0 (3.0, 6.5) kg. None of the infants was dependent on caffeine, oxygen or ventilator before surgery. Bradycardia (29/267, 10.9%) and postoperative desaturation (34/267, 13.4%) were identified as major cardiac and respiratory adverse events. Preoperative atropine, intubation and bigger body weight would prevent patients suffering from bradycardia. Infants with a body weight less than 3.15 kg had a significantly higher chance of desaturation and neonatal intensive care unit admission after ROP surgeries than those who weighed more than 3.15 kg (27.8% vs 5.1%, OR 5.46 (95% CI 2.66-11.21), P=0.000). Conclusion: This study found that preoperative atropine and intubation would prevent bradycardia and low body weight was a predictor for both bradycardia and postoperative desaturation in preterm infants undergoing ROP surgeries.